Determinants of Financial Performance among MSMEs in Jepara: The Role of Financial Management, Literacy, and Inclusion - Azizah, Shintanur; Widiastuti, Anna (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to determine the magnitude of the influence of financial management, financial literacy and financial inclusion on the financial performance of MSMEs in Jepara Regency. Methodology: This research uses a quantitative approach with a sampling technique, namely purposive sampling. The sample in the study was 113 MSME respondents in Jepara Regency. Technical data analysis using the IBM SPSS Statistics 25 program. Results: The analysis revealed that financial management had no significant effect on financial performance (β = 0.104, p = 0.378). In contrast, financial literacy (β = 0.354, p = 0.002) and financial inclusion (β = 0.277, p = 0.012) had a significant positive effect. The overall model explained 20.7% of the variance in financial performance (Adjusted R² = 0.207, F = 10.763, p < 0.05). Findings: Ease of access to financial services and good financial understanding can improve the financial performance of MSMEs. Novelty and Originality: While prior studies have explored the effects of financial literacy and inclusion in various regions, limited research focuses specifically on Central Java, particularly Jepara Regency. This study addresses that gap by providing empirical evidence that highlights the importance of financial literacy and inclusion in improving MSME competitiveness. Conclusion: Improving financial literacy and inclusive access to financial services is a key strategy for enhancing MSME financial performance. This study also recommends that local governments and financial institutions design practical financial education programs and simplify service access to better support MSMEs’ financial growth and resilience. Type of Paper: Research paper.